Nutritional Status and Associated Factors among Under Five Children of Slum and Non-Slum Area of Bharatpur Metropolitian City, Chitwan - Dhungana, Govinda Prasad; Wagle, Aakriti (BMC Journal of Scientific Research, 2018)
A cross-sectional and comparative study design was used to evaluate the nutritional status and associated factors among under five years’ children in Bharatpur Metropolitan City's slum and non-slum area. A total of 246 children under the age of 5 (each of 123 from slum and non-slum) were collected from April 1 to 30; 2017 was interviewed by face to face. Height and weight were measured by anthropocentric measurement and age was reported by direct interview for evaluation of nutrition status. The prevalence of wasted, stunted and underweight in the slum area was 4.9%, 28.5% and 6.5% respectively, whereas 4.9% wasted, 21.0% stunted and 5.7% underweight in the non-slum area. The study revealed that in slum as well as non-slum areas, the proportion of wasted was the same. Although maximum number of children in the slum had become stunted and underweight as compared to non-slums, but it was no statistically significant. Factors related to children: sex, early breastfeeding, colostrum feeding, birth weight, breastfeeding exclusiveness and children's number were statistically significant factors for nutritional status in slum while childhood diseases condition was associated factor in non-slum area. Mother related factors: mother occupation, mother height, age of child were associated factors in both settlement. Also, it reveled that that the joint effect was much stronger than the single effect to explorer the predictors of malnuttrition in both settlements.